(3GdCfSGHs - (3GdSeYGfj , YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj GdTGaYj GdMGaX, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3GdOhQbi HaJM GdOGd GdegedI hSchf GdhGh haJM GdQGA hai BNQgG GdbGa gPg GdfSHI GdJi JTjQ Edi HdOI HaGQS hbjd HNhQSJGf s
(3BNQgG (B:s
(3hSGdg GHfg ai hbJ GdfRY cja JQi bGd CQi cCf GdSeGA CWHbJ Ydi GdCQV hcGf faSi JNQL ef NQJ GHQI heGJ fLR GdeLdO GdQGHY s
(3fSNI KGfjIs
(3hgPg GdfSNI YdjgG JhbjY CMeO eHGQcTGg HedcjJg ddLRAs
(3jHJOF HGdOhQbi hjfJgi HGdgeis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs